THE USING OF PICTURE SERIES TO IMPROVE STUDENTS’ ABILITY AT WRITING DESCRIPTIVE TEXT FOR GRADE AT MAS YASPI LABUHAN DELI MEDAN - AR., M. Haddad Alqusyoi (Faculty of Tarbiyah nad Teacher Training, 2024)
The research aimed to evaluate the effectiveness of using picture series in teaching descriptive writing to students at X MAS YASPI Labuhan Deli. A qualitative approach was used, involving interviews, observations, and document analysis. The study found that using picture series is significantly more effective than traditional methods in improving students' descriptive writing skills. Picture series provide visual guidance and stimulate creativity, helping students express their ideas more clearly and structure their writing effectively. However, students faced challenges, including limited vocabulary, difficulty in organizing ideas, and a lack of understanding of descriptive text structure. Additionally, low motivation and interest in writing were also noted as obstacles. Despite these challenges, picture series proved beneficial by helping students understand the context, organize ideas, and develop more detailed, cohesive, and creative descriptive texts. The research concluded that picture series offer a visually stimulating and engaging method, significantly enhancing students' descriptive writing abilities. The findings will be published in a scientific journal and are expected to serve as recommendations for teachers and schools to incorporate picture series in teaching descriptive writing.Keywords: Picture Series, Writing Ability, Descriptive Text